Domenico Scarlatti’s В-Dur (К 266) Sonata: Special Features of Performing Interpretations - N. Yu. Zymohliad (Культура України, 2019)
The aim of this paper is to study the stylistic aspects of D. Scarlatti’s clavier works, to explore the performing interpretations of his B - dur (K 266) clavier sonata drawing on a note and music analysis. Particular attention is paid to an authentic performance by S. Ross and a piano performance by C. Grante. The study also aims at identifying the stylistic and artistic features of the performing interpretations presented. Research methodology. The author suggests a methodological substantiation of the characteristic features of D. Scarlatti’s clavier sonatas on the basis of a systemic approach and music analysis of B- dur (K 266) sonata by D. Scarlatti aiming at a comparative analysis of two interpretations, namely S. Ross’s and C. Grante’s ones. Results. Drawing on a music analysis the paper examines two interpretations of D. Scarlatti’s clavier B- dur (K 266) sonata, namely the authentic interpretation by S. Ross and the piano interpretation by C. Grante. Ascetism, the ability to perform each note and motive deliberately is characteristic to S. Ross’s interpretation. A slowly and rhythmical character corresponds to the author’s tempo instructions. In C. Grante’s interpretation one can feel the expressive variety of the work, which is enriched by the piano’s performing abilities. In his version, the sonata acquires the features of a character; the effect of the unity of two epochs is created, namely the past and the present. Like S. Ross, C. Grante follows the tempo instructions, but minimal slowdowns and accelerations add naturalness and “air” to the general movement. The author concludes that each of the performing interpretations presented demonstrates a new aspect of the sound image of D. Scarlatti’s B-dur (K 266) sonata. Architectonic harmony of S. Ross’s authentic interpretation with related performing features is stylistically different from the C. Grante’s dramatized interpretation. Each of the presented versions deserves attention and is of great artistic value. The practical significance consists in the analysis and comparison of the performing interpretations of D. Scarlatti’s clavier heritage (especially, insufficiently studied sonatas), as well as the study of the features of the composer’s clavier works. Key words: D. Scarlatti’s sonatas, D. Scarlatti’s clavier works, performing interpretations, authenticity, piano.